(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This is a rigorous study of Saturnino Osomio, one of the most representative personages in the history of Querétaro in the first decades of the 20th century. It is not so much a biography as a historical investigation that goes beyond the limits of the life and actions of this individual to insert him into a long process in which multiple social and political tensions can be perceived in direct relation to the articulation of the Mexican national State. In this multifaceted analysis, the author deals with forms of land tenure and their changes and continuities, as well as with the struggles of different sectors of society. In the same vein, she examines the revolutionary movement of 1910 and the new patterns of production and commercialization of Mexican agriculture that emerged in the aftermath of the mid-19th century liberal reforms that eroded the social tissue and gave new projection to a ranchero sector on the political stage.